2008
DOI: 10.1007/s00134-008-1230-5
|View full text |Cite
|
Sign up to set email alerts
|

Length of storage of red blood cells does not affect outcome in critically ill children

Abstract: Sir: Length of red blood cell (RBC) storage has been proposed a contributing factor to adverse outcome after RBC transfusion. This may be explained by an impaired ability to transport or deliver oxygen, or the presence of leukocytes in stored RBC preparations producing potential deleterious pro-inflammatory mediators or bioactive lipids [1]. We hypothesized that length of RBC storage might explain our previously observed independent association between RBC transfusion and increased mortality, duration of mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 6 publications
1
15
1
Order By: Relevance
“…These results are in agreement with other studies that demonstrated an association of red cell storage time with mortality and/or other adverse outcomes in postsurgical and trauma patients [11][12][13][14][15]. However, other studies found no significant differences in mortality and/or other outcomes in subjects treated with fresh or stored red blood cells [16][17][18][19]. The objective of the present work was to further assess potential benefits of fresh red blood cell transfusion, specifically in patients with septic shock.…”
Section: Introductionsupporting
confidence: 81%
“…These results are in agreement with other studies that demonstrated an association of red cell storage time with mortality and/or other adverse outcomes in postsurgical and trauma patients [11][12][13][14][15]. However, other studies found no significant differences in mortality and/or other outcomes in subjects treated with fresh or stored red blood cells [16][17][18][19]. The objective of the present work was to further assess potential benefits of fresh red blood cell transfusion, specifically in patients with septic shock.…”
Section: Introductionsupporting
confidence: 81%
“…In contrast to previous studies [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,18], the age of the transfused RBC units in the present study was invariably <14 days. Due to the institutional policy of using the freshest available blood units for pediatric patients, the individual storage times depended only on availability.…”
Section: Discussioncontrasting
confidence: 52%
“…An increase in infection rates and morbidity following transfusion of old blood has been described [2,3,4,5,6,7,8,9,10,11]. Other groups did not find a correlation between the storage time of transfused RBCs and patient outcome [12,13,14,15,16]. A possible explanation for these discrepancies may lie in the heterogeneity of the study designs and patient groups, the use of different outcome parameters, and the various cut-offs of RBC age (5-27 days).…”
Section: Introductionmentioning
confidence: 99%
“…Others reported no significant clinical impact with transfusion of older RBC units [22-25,32]. The only pediatric study evaluating the effect of RBC unit length of storage on outcome was a post-hoc analysis by Kneyber and colleagues [26]. They reported no differences in length of ventilation, PICU length of stay, or death rate in a small number of transfused patients (n = 67).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in these conflicting studies, which include baseline severity of illness of patients studied and sample size issues, make comparing these studies difficult. Only one small retrospective study has assessed the effect of RBC length of storage on outcomes in children and no relation was found between RBC unit length of storage and clinical outcome in critically ill children [26]. …”
Section: Introductionmentioning
confidence: 99%